2007
DOI: 10.1359/jbmr.070711
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Monoclonal Antibody Raised Against Nerve Growth Factor on Skeletal Pain and Bone Healing After Fracture of the C57BL/6J Mouse Femur

Abstract: A closed femur fracture pain model was developed in the C57BL/6J mouse. One day after fracture, a monoclonal antibody raised against nerve growth factor (anti-NGF) was delivered intraperitoneally and resulted in a reduction in fracture pain-related behaviors of ∼50%. Anti-NGF therapy did not interfere with bone healing as assessed by mechanical testing and histomorphometric analysis.Introduction: Current therapies to treat skeletal fracture pain are limited. This is because of the side effect profile of availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
115
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(124 citation statements)
references
References 114 publications
(239 reference statements)
9
115
0
Order By: Relevance
“…In order to assess bone pain severity associated with MTX chemotherapy, we adopted some well established animal behavioural tests for measuring bone pain induced by bone cancer and fracture [18,20]. These tests were designed to assess ongoing and breakthrough pain, the two most clinically recognized types of pain due to bone damage [24,25].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to assess bone pain severity associated with MTX chemotherapy, we adopted some well established animal behavioural tests for measuring bone pain induced by bone cancer and fracture [18,20]. These tests were designed to assess ongoing and breakthrough pain, the two most clinically recognized types of pain due to bone damage [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…These animal behavioural tests (outlined in Fig. 1) are based on well-established protocols routinely used to assess cancer and fracture-induced bone pain in rats and mice [16][17][18][19][20][21].…”
Section: Animal Behavioural Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…NGF is a neurotrophin, which is released from inflamed tissue and sensitizes peripheral nociceptors. Animal models have shown that by blocking the action of NGF with a soluble receptor or monoclonal antibody, pain can be significantly reduced 10,11 . …”
Section: Pain Is the Overriding Clinical Issue In Osteoarthritis (Oa)mentioning
confidence: 99%